The relationship between the central government and local administrations in the federal system: Experience the Iraqi model - جواد علاء الدين برع (Journal of Economics and Administrative Sciences, 2018)
Increasingly, public organizations in the federal state are required to work together, as well as to work with others to achieve their objectives. In Iraq there are two levels of organizations, including federal and local, and these organizations have been forced to work for many years in an environment in which the responsibility for service delivery is shared between policy makers and service providers, and between local governments and the federal government. It is sometimes difficult to manage the relationship between these organizations (federal and local) and do not always provide the best possible outcome of this relationship. This paper reviews how to manage the relationship between local administrations and the federal government in the federal system with a focus on the Iraqi experience. And illustrate examples of how to develop cooperation, exchange and terms of reference. The researcher reached conclusions and recommendations whose main purpose is to streamline the relationship between the federal government and local administrations to reach the desired goal of their respective existence.